Peningkatan Hasil Belajar Fisika Siswa Kelas X Melalui Implementasi Model Pembelajaran Reciprocal Teaching Di SMAN Negeri 9 Padangsidimpuan - Ahsanul Arifin; Sri Utami Kholilla Mora Siregar; Eni Sumanti Nasution (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
The aim of the research is to determine the improvement in physics learning outcomes for Class X students through the implementation of the Reciprocal Teaching Learning Model at SMA Negeri 9 Padangsidimpuan. The formulation of the problem in this research is whether there is an increase in physics learning outcomes for Class X students through the implementation of the Reciprocal Teaching Learning Model at SMA Negeri 9 Padangsidimpuan? The sample in this research was students of XI SMAN 9 Padangsidimpuan with a total of 25 students. The instruments in test research explain that the type of research is Classroom Action research. Data analysis techniques use normality tests, reduction, data presentation and reflection. Analysis results. Student learning outcomes increased. After knowing the comparison of learning outcomes, there was also an increase in the number of students who completed the pre-cycle (59.50), cycle I (70.17) and cycle II (81.67). and completeness of learning outcomes for Pre-cycle (4 people), Cycle I (14 people) and Cycle II (22 people).